Developing Problem Solvers: An Activity-Based Intervention Approach for Adolescents - Paul, Madhumita; Chakraborty, Soumen (Journal of Educational Research and Policies, 2025)
Problem-solving ability is a critical cognitive skill that significantly influences academic success and everyday decision- making in adolescents. Enhancing this skill during adolescence can lead to better outcomes in both personal and professional aspects of life. This study investigates the impact of targeted mental workouts on the problem-solving abilities of adolescents. Utilizing a pre-post experimental control group design, 240 adolescents were randomly assigned to either an experimental group, which received the mental workout intervention, or a control group, which did not. The intervention consisted of structured activities designed to enhance cognitive functions related to problem-solving. Pre-intervention assessments established a baseline of problem-solving abilities for both groups. Following the intervention period, post-intervention assessments revealed that the experimental group demonstrated significant improvements in problem-solving skills compared to the control group. These findings underscore the effectiveness of targeted mental exercises in enhancing cognitive capabilities in adolescents, suggesting potential applications for educational and developmental programs.